Reformasi Pendidikan Islam dan Implikasinya Prespektif Pemikiran Pendidikan Filsuf Islam - Zainal Arifin; Moh. Hasyim Afandi (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
This study wants to describe the concept of educational thought according to some Islamic education figures, in relation to efforts to reform Islamic education and its implications in Islamic education today. The results of this study include: The aim of Islamic education must lead to purification of the soul to go to taqarub to Allah Almighty who will ultimately get the happiness of the world and the hereafter. Teacher / Educator Modeling is a necessity in education, because students are more easily influenced by imitation and emulation and noble values ​​that they witness, than can be influenced by advice, teaching. (Spiritual, paedagogie, professional, social, personality and innovative competencies). Students are likened to people who have not been educated in Islamic creed like paper that is still pure white, has not been tarnished in any way. If this paper is written something, then the paper has a mark that is not easily removed. This view is closer to the theory of Tabula Rasa John Locke (empiricism).